Interleukin-1β regulates CFTR expression in human intestinal T84 cells - Cafferata, Eduardo Gustavo Alfredo (2000)
Cystic fibrosis is an autosomal recessive genetic disease, produced by a mutation in the CFTR gene that impairs its function as a chloride channel. In this work, we have examined the effects of interleukin-1β (IL-1β) on the expression of CFTR in human colonic T84 cells. Treatment of T84 cells with IL-1β (0.25 ng/ml) for 4 h resulted in an increased CFTR expression (mRNA and protein). However, higher doses of IL-1β (1 ng/ml and over) produced inhibition of CFTR mRNA and protein expression. The protein kinase C (PKC) inhibitors H7 (50 μM) and GF109203X (1 μM) inhibited the stimulatory effect of IL-1β. Similar effects were seen in the presence of the protein tyrosine kinase (PTK) inhibitors genistein (60 μM) and herbymicin A (2 μM). These results suggest that some PKC isoform(s) and at least a PTK might be involved in the CFTR up-regulation induced by IL-1β. The repression of CFTR up-regulation by cycloheximide (35.5 μM) suggests the participation of a de novo synthesized protein. Results obtained by using the RNA polymerase II inhibitor DRB (78 μM), suggest that the increased mRNA levels seen after IL-1β treatment are not due to an increased stability of the message. We conclude that the CFTR mRNA and protein levels are modulated by IL-1β, this cytokine being the first extracellular protein known to up-regulate CFTR gene expression.